The Effect of Capital Structure Moderating Receivable Turnover and Inventory Turnover on Profitability - Rika Nur Ainia; Indah Yuliana (Poltanesa, 2023)
Receivable and inventory control in carrying out the company's activities is very important in order to achieve the company's vision and mission. This study aims to find out how the effect of receivable turnover and inventory turnover on the profitability of the company with the capital structure as a moderation variable. The population of this study was a company listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2019, the sample for this research consists of nine companies in the consumer goods, basic industries, and chemical sectors selected by purposive random sampling. The analysis method used was descriptive statistics with analysis tools using Partial Least Square (PLS) approach. The PLS-SEM analysis technique uses the help of WarpPLS 6.0 software with two stages of analysis, namely Measurement Model Analysis and Structural Model Analysis. Evaluation of the Outer Measurement Model uses three evaluation models, namely: Convergent Validity, Discriminant Validity, and Reliability Test. The results of this study showed that there was a significant positive influence between the turnover of receivables to profitability while inventory turnover has a significant negative effect on profitability and variable capital structure is not able to moderate the relationship between receivable turnover and inventory turnover to profitability.